PROSES AKTIVITAS DALAM PENGEMBANGAN KOLEKSI DI PERPUSTAKAAN UNIVERSITAS POTENSI UTAMA MEDAN - Idzhari Rahman (Central Library of Universitas Sebelas Maret, 2019)
This paper is focusing on the availability of colection in University Library and how the concept of developing the colection activity. The purpose is to understand deeply in developing the colection activity in University Library. The success of university library in developing the colection is determined by three stages: 1) doing the analysis toward Librarian, 2) library’s policy of developing the colection, 3) doing the selection of library material, 4) acquisition, the activity of procument the library colection, 5) weeding colection activity because it is unrelevant with the need of librarian, and 6) always doing evaluation toward the library’s colection due to fulfill the need of librarian. The library in university has to anticipate the problem that is faced in developing the library colection and library should provide adequate sources due to lauch the process of developing the colection in order to effort the continuity and acceleration of developing the colection. library’s consistency is expected to be effective program and have a certain quality in developing the library colection.